(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Over the years, the changing purchasing habits of Indian consumers have seen a tremendous transition. A better state of the economy, exposure to international media, travel abroad, the degree of urbanisation, educational attainment, and the introduction of new employment prospects in the service sector, such as in information technology. Some of the drivers include call centres and shopping that affects consumer habits. Due to economic changes implemented two decades ago, the middle class has grown significantly. In India, altering spending habits are occurring as disposable income rises. For international beverage manufacturers, India’s beverage industry is a significant market. The food sector in India is extremely profitable thanks to rising standards of living and population expansion. Indian society’s traditional economic environment was different from its current environment. The majority of Indian consumers gave home-cooked cuisine a strong preference. Contrarily, the current practise of eating out is quickly altering Indian society’s perspective. Due to the fast-paced modern lifestyle, hectic schedules, competition, rise in the number of working women, nuclear family concept, etc., many fast-food franchises have now established themselves in India.